Desain Bahu Jalan Letjen S. Parman, Kelurahan Panjer, Kecamatan Denpasar Selatan, Kawasan Niti Mandala Renon Denpasar - Bali - Natanael, Neil Haezer; Sugianthara, Anak Agung Gede; Kohdrata, Naniek (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022DO - 10.24843/JAL.2022.v08.i01.p08, 2022)
Letjen S. Parman Roadside design, Sumerta Kelod, County District East Denpasar. Denpasar is one out of nine districts/cities and it is the most populated in Bali Province. Rapid population growth leads to an increase in its population density that affects traffic growth in Denpasar City. Letjen S. Parman is one of the business district roads in the Renon Field area located in the heart of Denpasar City that is often used for public with or without vehicles, which makes this area dense and requires a balance of infrastructure and supporting traffic signs and signals to ensure safety and enhance convenience. Roadsides of Letjen S. Parman Road is still often converted by the public into a parking space and a marketplace. The purpose of this study was to research traffic rules along Letjen S. Parman road and users’ opinions on it. Methodology employed to conduct the study was direct survey and collecting the data by direct field observations, interviews, and questionnaires. The research revealed that, according to traffic laws, Letjen S. Parman roadsides were not supposed to be misused by road users. Pedestrians who use Letjen S. Parman roadsides also feel disturbed by road users who inappropriately turned them into parking spots or a marketplace. The result of the study is related to design recommendations to solve traffic problems along Letjen S. Parman Road as well as a point of reference for relevant agencies and government officials.